Design and Experiment of a PLC-Based Intelligent Thermal Insulation Box for Nursing Piglets - Bin Sun; Hao Wang; Xuemin Pan; Yaqiong Zeng; Bin Hu; Renli Qi; Dingbiao Long; Shunlai Xu (Animals)
Local heating of the activity area for nursing piglets is crucial for piglet health and the energy efficiency of barn climate control. Traditional heating methods using lamps or covers lack precise control, result in significant energy waste, and cannot be dynamically adjusted according to piglet age or changing environmental temperatures. To address these issues, this study designed a Programmable Logic Controller (PLC)-based thermal insulation box for nursing piglets, utilizing a strip heater instead of the conventional round heating lamp. The design incorporates a movable thermal insulation box that dynamically adjusts the heater’s power based on the real-time monitoring of environmental temperatures and target temperatures specific to piglet age. First, in a controlled laboratory environment, the study tested and compared the spatial temperature uniformity, temporal stability, and power consumption of the new thermal insulation box versus traditional heating methods. Subsequently, animal trials were conducted in a farrowing barn using eight sows with similar farrowing dates as test subjects. The new thermal insulation box was installed in one group, and the traditional heating lamp in the control group. During the trial, ambient temperature, insulation area temperature, piglet behavior, growth performance, and power consumption were recorded. The results showed that compared to the control group, the new system reduced average temperature fluctuations in the insulation area by 31.6% and spatial temperature variation by 78.3%. During animal trials, the average temperatures directly under the heater for the new system versus the control in the insulation area were 39.7 ± 0.2 °C and 30.2 ± 1.4 °C in the first week, 40.9 ± 0.5 °C and 31.6 ± 0.7 °C in the second week, and 32.3 ± 1.5 °C and 28.6 ± 1.7 °C in the third week—significantly (p < 0.05) higher in the test group. The new system also reduced total energy consumption by 58.3%. The usage rate of the thermal insulation area by piglets in the test and control groups was 47.5 ± 5.3% and 42.1 ± 6.6%. The daily weight gain of piglets in the test group was 9.8% higher than that of the control group, also significantly (p < 0.05) higher. This intelligent thermal insulation box enables precise and dynamic temperature control, reducing heating energy consumption and supporting improved piglet health and welfare.